Lesões traumato-ortopédicas e percepção da qualidade de vida em atletas de basquetebol em cadeira de rodas - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The aim of this study was to analyze the relationship between the presence of traumatic orthopedic injuries and quality of life (QoL) perception in Wheelchair Basketball (WCB) players. Fifty-eight WCB athletes with a mean age of 35.75 (± 11.21) years, who practiced the modality for 6.18 (± 4.83) years, participated in the study. The frequency and distribution of traumatic orthopedic injuries occurred in the last 12 months (which resulted in any restriction in sports participation or performance) was verified using a questionnaire adapted from the instrument developed by the Laboratory for the Prevention and Rehabilitation of Sports Injuries (LAPREV-MG) and the instrument used by the National Injury Recording System (NAIRS). The WHOQOL-bref and the WHOQOL-DIS-PD additive module were used to assess the athletes' QoL perception. The strength and direction of the association between the dependent variable (QoL perception) and independent variables (presence of injury and sociodemographic information) were analyzed using the Poisson regression test. The odds ratio was calculated to determine how many times the chance of a WCB athlete with or without injuries present unsatisfactory QoL. All statistical treatment was performed through the SPSS program, version 15.0 for Windows. Significant associations were found between QoL perception and health status; and between the presence of injuries and time of WCB, use of the wheelchair, parallel training and use of crutch or cane. The analyzes showed that the higher the age of the athletes, the lower their perception of the environment domain. On the other hand, the longer the WCB practice time, the more satisfied the athletes are in relation to the social support domain. There was no association between the presence of lesions and the perception of QoL among the investigated athletes.
Keywords: Pessoas com deficiência; Qualidade de vida; Lesões esportivas; People with disabilities; Quality of life; Sports injuries; CNPQ::CIENCIAS DA SAUDE